Streets of fire Bruce Springsteen in photographs and lyrics, 1977 - 1979 - Springsteen, Bruce 1949- (ItBooks, 2012)
Photographs of the musician from 1977-1979, interspersed with full lyrics, lyric selections, and essays by the photographer